Anti-tumour activity of everolimus and sunitinib in neuroendocrine neoplasms. Issue 6 (June 2019) - Daskalakis, Kosmas; Tsoli, Marina; Angelousi, Anna; Kassi, Evanthia; Alexandraki, Krystallenia I; Kolomodi, Denise; Kaltsas, Gregory; Koumarianou, Anna
Abstract : Comparisons between everolimus and sunitinib regarding their efficacy and safety in neuroendocrine neoplasms (NENs) are scarce. We retrospectively analysed the clinicopathological characteristics and outcomes in 92 patients with well-differentiated (WD) NEN of different origin (57 pancreatic NENs (PanNENs)), treated with molecular targeted therapy (MTT) with everolimus or sunitinib, first- (73:19) or second-line (sequential; 12:22) for progressive disease. Disease control rates (DCR: partial response or stable disease) at first-line were higher in all patients treated with everolimus than sunitinib (64/73 vs 12/19, P = 0.012). In PanNENs, DCR at first-line everolimus was 36/42 versus 9/15 with sunitinib ( P = 0.062). Progression-free survival (PFS) at first-line everolimus was longer than sunitinib (31 months (95% CI: 23.1–38.9) vs 9 months (95% CI: 0–18.5); log-rank P < 0.0001) in the whole cohort and the subset of PanNENs (log-rank P < 0.0001). Median PFS at second-line MTT was 12 months with everolimus (95% CI: 4.1–19.9) vs 13 months with sunitinib (95% CI: 9.3–16.7; log-rank P = 0.951). Treatment with sunitinib (HR: 3.47; 95% CI: 1.5–8.3; P value: 0.005), KI67 >20% (HR: 6.38; 95% CI: 1.3–31.3; P = 0.022) and prior chemotherapy (HR: 2.71; 95% CI: 1.2–6.3; P = 0.021) were negative predictors for PFS at first line in multivariable and also confirmed at multi-state modelling analyses. Side effect (SE) analysis indicated events of serious toxicities (Grades 3 and 4: n = 13/85 for everolimus and n = 4/41 for sunitinib). Discontinuation rate due to SEs was 20/85 for everolimus versus 4/41 for sunitinib ( P = 0.065). No additive toxicity of second-line MTT was confirmed. Based on these findings, and until reliable predictors of response become available, everolimus may be preferable to sunitinib when initiating MTT in progressive NENs.